Identification and Characterization of New Long Chain Acyl-CoA Dehydrogenases - He, Miao (2010)
Long-chain fatty acids are an important source of energy in muscle and heart where the acyl-CoA dehydrogenases (ACADs) participate in consecutive cycles of β-oxidation to generate acetyl-CoA and reducing equivalents for generating energy. However, the role of long-chain fatty acid oxidation in the brain and other tissues that do not rely on fat for energy is poorly understood. Here we characterize two new ACADs, ACAD10 and ACAD11, both with significant expression in human brain. ACAD11 utilizes substrates with primary carbon chain lengths between 20 and 26, with optimal activity towards C22CoA. The combination of ACAD11 with the newly characterized ACAD9 accommodates the full spectrum of long chain fatty acid substrates presented to mitochondrial β-oxidation in human cerebellum. ACAD10 has significant activity towards the branched-chain substrates R and S, 2 methyl-C15-CoA and is highly expressed in fetal but not adult brain. This pattern of expression is similar to that of LCAD, another ACAD previously shown to be involved in long branched chain fatty acid metabolism. Interestingly, the ACADs in human cerebellum were found to have restricted cellular distribution. ACAD9 was most highly expressed in the granular layer, ACAD11 in the white matter, and MCAD in the molecular layer and axons of specific neurons. This compartmentalization of ACADs in the human central nerve system, suggests that β-oxidation in cerebellum participates in different functions other than generating energy, for example, the synthesis and/or degradation of unique cellular lipids and catabolism of aromatic amino acids, compounds that are vital to neuronal function.